Human Papilloma Virus (HPV) Infection And HPV Vaccination: A KAP Study Among Adolescents, Adults And Parents - Ali, Abdul Nazer (2017)
Baseline information on knowledge, attitude and perception towards Human Papilloma Virus (HPV) infection is crucial to establish a progressive track of practice on HPV immunization program to defeat the challenges. The present study aimed at developing population specific intervention tool (questionnaires) including informative educational tool (pamphlet) and to assess the impact of these tools on knowledge, attitude, perception and/or practice (KAP) changes among the three study populations (adolescents, adults and parents). A prospective cross sectional study was conducted in urban and rural areas of Kedah state, Kedah Malaysia.